Smart Borders - Cimadomo, Guido; Martínez Ponce, Pilar (Center for the Study of Development Societies (CSDS), 2007)
Borders, as we know them today, are created most of times in war situations, and they are kept alive for the capacity of a credible response to a possible invasion. Only with the arrival of the globalization, which we can make coincide with the fall of the wall of Berlin in 1989, and with the development of the different supranational entities destined for the control and development of the trade (WTO), the borders acquire a strategic importance in the control of different flows, especially economic and migratory ones. We want to propose borders as porous systems, technologicals, but especially three-dimensionals, conforming themself as bridges between the different shores, a few antennas that not only catch and attract the forces of both realities, but also transmit to every side the realities, cultures and traditions of the inhabitants. We want to return to the concept of the old great bazaar, a place where persons on both sides of the border can meet, generating a new place of interchange (cultural, economic...). We think about the utilization of zeolites, or smart sponges as a metaphor of the functioning of these spaces: microporous solids with the aptitude to store selectively and then to return heat, water, gas, or even people and dreams.
Keywords: Fronteras; Border; Border transformation; Smart border